Atomically Defined Undercoordinated Active Sites for Highly Efficient CO2 Electroreduction. (4th November 2019) - Zheng, Wanzhen; Yang, Jian; Chen, Hengquan; Hou, Yang; Wang, Qi; Gu, Meng; He, Feng; Xia, Ying; Xia, Zheng; Li, Zhongjian; Yang, Bin; Lei, Lecheng; et al.
Abstract: Electrocatalytic reduction of carbon dioxide (CO2 ER) in rechargeable Zn–CO2 battery still remains a great challenge. Herein, a highly efficient CO2 ER electrocatalyst composed of coordinatively unsaturated single‐atom copper coordinated with nitrogen sites anchored into graphene matrix (Cu–N2 /GN) is reported. Benefitting from the unsaturated coordination environment and atomic dispersion, the ultrathin Cu–N2 /GN nanosheets exhibit a high CO2 ER activity and selectivity for CO production with an onset potential of −0.33 V and the maximum Faradaic efficiency of 81% at a low potential of −0.50 V, superior to the previously reported atomically dispersed Cu–N anchored on carbon materials. Experimental results manifest the highly exposed and atomically dispersed Cu–N2 active sites in graphene framework where the Cu species are coordinated by two N atoms. Theoretical calculations demonstrate that the optimized reaction free energy for Cu–N2 sites to capture CO2 promote the adsorption of CO2 molecules on Cu–N2 sites; meanwhile, the short bond lengths of Cu–N2 sites accelerate the electron transfer from Cu–N2 sites to *CO2, thus efficiently boosting the *COOH generation and CO2 ER performance. A designed rechargeable Zn–CO2 battery with Cu–N2 /GN nanosheets deliver a peak power density of 0.6 mW cm −2, and the charge process of battery can be driven by natural solar energy. Abstract : Highly efficient Cu–N2 sites for CO2 electroreduction: an ultrathin Cu–N2 /GN nanosheet with highly exposed and coordinatively unsaturated Cu–N2 active sites is developed for highly efficient CO2 reduction to CO.